Peran Perempuan dalam Komunikasi Dakwah Islam: Kritik Literatur terhadap Studi-Studi Terdahulu - Saha , Nova; Karisna, Nila Noer (Jisab, 2024)
This research aims to further explore the role of women in Islamic preaching communication. The study adopts a qualitative approach with a literature review design. Data collection techniques involve documentation and observation, with analysis utilizing data condensation, data collection, and conclusion drawing. The results of the literature review indicate seven roles of women in Islamic preaching communication. First, women play a role as disseminators of religious messages in their communities. Second, they serve as activists in preaching activities within social and community settings. Third, women also have a significant role in utilizing social media and information technology to disseminate preaching messages. Fourth, they can act as mediators in interfaith and intergroup dialogues, aiming to strengthen tolerance and harmony among religious communities in Indonesia. Fifth, women contribute to educating the younger generation about Islamic values and morals. Sixth, women can also act as agents of change in society through social and political activism based on Islamic principles. Seventh, women can also take on leadership roles in Islamic-based religious and community institutions.